Transformasi Pendidikan Islam di Era Smart Society 5.0: Strategi Kepala Madrasah untuk Meningkatkan Pembelajaran Guru pada Lembaga Pendidikan Islam - Wahyudin, Aji; Rizki, Aulia; Nasirudin, Humam; Prayogi, Lutfi Setya (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Abstract. The purpose of this study is to reveal the principles of madrasas in improving teacher learning in the era of smart society 5.0. The principal's strategy for improving teacher learning must be acceptable and relevant to student learning objectives. This study uses the results of a literature review of several sources. The results show that the principal's method for improving teacher learning is to carry out a series of activities in the form of professional services to assist teachers in developing their abilities (competencies) to better manage the learning process. In an era of disruption where all digital channels are added, plus very fast access to information, the teacher is the central point of improving the quality of education as an impact on the quality of the learning process, teacher professionalism needs to continue to grow and develop so that teachers can carry out their duties professionally. Several methods can be used and implemented by school principals by focusing on the needs of students and streamlining the function of the principal as a leader, supervisor, and manager in the madrasa by applying them through the development of the Smart Society 5.0 era which demands the use of digitalization technology.